State Programming of Innovation Development of Economy: Macrostructural Priorities, Institutional and Economic Specification - GORDEEVA, Elena; ESENGELDIN, Baurzhan; KHUSAINOVA, Zhibek (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The article deals with the problems of the effectiveness of state programming of innovative development of the national economy. The authors study the traditional program-target approach in the activation of the country's innovative development; identify the features, functional nature and macrostructural priorities of different country versions of state innovation development programs. In addition, taking into account foreign experience and from the position of strategic growth in the Kazakhstan economy, the accumulative picture of macroeconomic priorities in the mainstream innovative development is revealed. The authors emphasize that the evaluation of the effectiveness of innovative development programs has a number of features that are associated with specific features of innovation. Based on the analysis of the experience of the Republic of Kazakhstan in the development and implementation of state programs of industrial and innovative development, their institutional and economic specification is specified, their applied effectiveness is assessed, and the basic reasons for the inhibition of innovation in the domestic economy and miscalculations in the field of state programming are identified.